The Effectiveness of Implementing P5 to Develop Independent Character Education for Children at Aisyiyah Gesi Kindergarten - Anis Noviyanti; Wili Astuti (Universitas Muhammadiyah Surakarta, 2025)
The purpose of this study was to determine the effectiveness of the Pancasila Student Profile Strengthening Project (P5) in increasing the independence of Aisyiyah Gesi Kindergarten children. This study used a pre-experimental design method with one group pretest-posttest type. Data collection techniques were tests and documentation. The research subjects were 15 Aisyiyah Gesi Kindergarten students. The data analysis technique used was the SPSS version 22 program. The results of this study concluded that the level of children's independence abilities before being given treatment (pretest) was 10.2 while after treatment the average child's independence was 18.8. The results of the hypothesis test (t-test) showed a significance value (sig. The sig value is 2 where the significant value (p-Value) <0.05 means that the P5 Project has a real influence on children's independence. Thus, it can be concluded that Ha is accepted and Ho is rejected, which means there is an influence on the effectiveness of the Pancasila Student Profile Strengthening Project (P5) in increasing the independence of Aisyiyah Gesi Kindergarten children.